Research on isokinetic shoulder strength testing of female elite swimmers - Chang, S.; Cheng, L.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the shoulder muscle strength characteristics of the female elite swimmers in Sichuan province, find out specific weakness part of their shoulder joint strength . Using IsoMed 2000 isokinetic dynamometer measured the shoulder muscle strength for the subjects(n=15) of the shoulder flexors, extensors, adductor and abductor at the different angular velocities, then analyzed the problem in the subjects' shoulder strength training, the result showed that:there is a significant difference(P <0.01) about the muscle strength endurance ratio between two sides of the shoulder extensors and flexors, and the extensors strength rate of decline is less than flexors. The information has important significance for improving athletic performance and preventing subjects from shoulder injury.